PREVENTION OF ONCOLOGICAL DISEASES AS THE BASIS OF INTERACTION OF ONCOLOGICAL SERVICE WITH PRIMARY LINK OF HEALTH CARE - L. M. Aleksandrova; V. V. Starinsky; A. D. Kaprin; Yu. V. Samsonov (Исследования и практика в медицине)
Malignant neoplasms (MN) are the second cause of death for the population of Russia, resulted in 15.5% of all deaths in 2015. Their share in the structure of the male population mortality rate was 16.4%, female — 14.4%. Among both sexes, deaths of working age, the proportion of deaths from MN was 16.0%, among women of reproductive age — 16.3%. More than half of the working age population of deaths in Russia falls on the disease from the group of preventable death, and a third — to preventable causes, depending on the primary and secondary prevention, quality of care, along with a high prevalence of behavioral risk factors (RF), demographic characteristics, marked medical and social reasons for the high mortality rate of the MN: late uptake of the population for health care, lack of alertness in oncology healthcare professionals, patients defects in routing.The leading factor in increasing life expectancy is prevention. Today, prevention is regarded as active method of strengthening and preservation of health, and the currently existing approaches in promoting healthy life mostly only directed at the prevention of behavioral risk factors: tobacco use, poor diet, physical inactivity and harmful use of alcohol. Experts estimate the impact on them will prevent, at least 40% of the cases of MN.In Russia we have a 3-step system of health care. In general preventive health orientation is implemented on the 1st level: in the provision of primary health care. In this regard, particular attention should be paid to the implementation of measures for specific clinical examination of the adult population, which plays an important role in the early detection of both the disease and the risk factors for their development. Properly organized conduct of the clinical examination can provide a substantial, up to 30%, the contribution to the reduction of total mortality, including mortality from MN. The necessity of increasing the role of the oncology service in the organizational and methodological support of the preventive measures implemented by primary health care is performed.